A learning study on volunteering in the emergency recovery system in Russia: on the interaction between the state and civil organizations - Zaitseva, Irina Aleksandrovna (2020)
The purpose of the article is to identify the motives, types, and areas of volunteering in the system of emergency response in the Lipetsk region, Russia. To obtain quantitative characteristics of the problem studied, we have used the method of mass polling at the place of residence, work, and study of respondents. The main motive for participants in volunteer activities is the altruistic reason. 8.1% of volunteers have defined their sphere of activity as volunteerism in emergencies. 31.9% are potentially ready to help people in emergency situations. This variance in figures we could explain by the fact that many volunteers do not have enough necessary skills. Besides, the participation in emergency situations liquidation, traffic accidents, fire extinguishing, etc., is associated with possible risk.